2017
DOI: 10.1002/tea.21431
|View full text |Cite
|
Sign up to set email alerts
|

Positioning as not‐understanding: The value of showing uncertainty for engaging in science

Abstract: Not understanding is central to scientific work: what scientists do is learn about the natural world, which involves seeking out what they do not know. In classrooms, however, the position of not‐understanding is generally a liability; confusion is an unfortunate condition to resolve as quickly as possible, or to conceal. In this article, we argue that students' public displays of uncertainty or confusion can be pivotal contributions to the classroom dynamics in initiating and sustaining a class's science inqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 52 publications
(78 reference statements)
2
62
2
2
Order By: Relevance
“…This course was an instance in general support of those principles: both the launching questions and the reasoning it elicited “problematized subject matter” (cf. Watkins, Hammer, Radoff, Jaber, & Phillips, ); in this course as in other responsive teaching, the students had authority to address problems; and the interactions held them accountable to disciplinary norms, such as of providing evidence to support claims or expressing ideas in clear, understandable terms.…”
Section: Discussionmentioning
confidence: 95%
“…This course was an instance in general support of those principles: both the launching questions and the reasoning it elicited “problematized subject matter” (cf. Watkins, Hammer, Radoff, Jaber, & Phillips, ); in this course as in other responsive teaching, the students had authority to address problems; and the interactions held them accountable to disciplinary norms, such as of providing evidence to support claims or expressing ideas in clear, understandable terms.…”
Section: Discussionmentioning
confidence: 95%
“…Drawing from the social framing perspective, Watkins et al () suggested that the practice of social negotiation provides opportunities for students to position themselves as “not‐understanding,” not only allowing them to articulate their uncertainty in the argument but also creating space for sense‐making around a phenomenon. Phillips, Watkins, and Hammer () referred to this social negotiation practice as a “problematizing activity” in which students identify inconsistency of their understanding and articulate their uncertainties in order to develop more cohesive and coherent knowledge (p. 984).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Jordan and Babrow () contended that “uncertainty is vital to the learning process” (p. 211) because uncertainty creates moments “where students struggle to learn new knowledge and skills, adopt new practices, and come to new understandings” (Jordan, , p. 99). Through creating moments of uncertainty, students can “express unease about their own understanding and then articulate gaps or inconsistencies” between that and target scientific knowledge (Watkins, Hammer, Radoff, Jaber, & Phillips, , p. 593).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as Watkins, Hammer, Radoff, Jaber, and Phillips () argued, “not understanding is central to scientific work” (p. 573); scientists know that “confusion, ambiguity, or uncertainty” (p. 573) are often central to coming to understand. Yet, conventional science classroom thinking and practices highly value knowing and correct answers, thus making a lack of understanding a liability as well as an “uncomfortable social position in classrooms” (Watkins, Hammer, Radoff, Jaber, & Phillips, , p. 574). An analogous process occurs in our research on science teaching and learning, particularly when engaging in participatory methods.…”
Section: Ethical Considerations When Utilizing Participatory Researchmentioning
confidence: 99%